Quality of Life after Open versus Closed Treatment for Mandibular Condylar Fractures - Samreena,; Alam, Jehan; Shah, Ruqaya; Ahmed, Javeria; Zain, Anosha; Sheikh, Zulakha Akhtar (Indus Journal of Bioscience Research, 2024)
Objective: To compare the quality of life after surgical management with closed reduction and internal fixation (CRIF) versus open reduction and internal fixation (ORIF) for mandibular condylar fractures. Methodology: This analytical observational study was carried out between January 2024 to June 2024, at the Department of Oral and Maxillofacial Surgery, Jinnah Postgraduate Medical Centre, Karachi, focusing on patients with mandibular condylar fractures. The study assessed their quality of life using the General Oral Health Assessment Index (GOHAI) Questionnaire, with scores ranging from 1 to 3, where 1 denoted "Always," 2 indicated "Sometimes," and 3 represented "Never." Quality of life scores were categorized as high (34-36), medium (31-33), or low (<30) based on the GOHAI results. Results: In this study there were 66.7% neglected patients had high quality of life, 15.4% had moderate, and 27.3% had low GOHAI, (p=0.084). Further, there were only 16.7% patient close reduction management had high quality of life, 5 (38.5%) had moderate, and 545.5% had low GOHAI. According to open reduction management, there were 83.3% patients had high quality of life, 61.5% had moderate, and 45.5% had low GOHAI, (p=0.157). Conclusion: Factors such as age, gender, neglected type, and treatment modality did not significantly affect the post-operative quality of life. However, mandibular fracture patients who underwent surgical treatment with open reduction technique, as assessed by the GOHAI parameter, experienced a high quality of life.